2020
DOI: 10.3390/ijms21228740
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining and Evaluation of the Biocontrol Potential of Pseudomonas fluorescens BRZ63, a New Endophyte of Oilseed Rape (Brassica napus L.) against Fungal Pathogens

Abstract: Endophytic bacteria hold tremendous potential for use as biocontrol agents. Our study aimed to investigate the biocontrol activity of Pseudomonas fluorescens BRZ63, a new endophyte of oilseed rape (Brassica napus L.) against Rhizoctonia solani W70, Colletotrichum dematium K, Sclerotinia sclerotiorum K2291, and Fusarium avenaceum. In addition, features crucial for biocontrol, plant growth promotion, and colonization were assessed and linked with the genome sequences. The in vitro tests showed that BRZ63 signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 93 publications
0
25
0
Order By: Relevance
“…To enhance the bioavailability of hydrocarbons, microorganisms produce biosurfactants [ 107 , 108 ]. The biosurfactants produced by bacteria can also contribute to inhibiting the growth of phytopathogens, help colonize plant tissues and improve bacterial motility [ 109 ]. In this study, the ZCR6 strain produced a surface-active compound, which showed a positive result for the oil-spreading test and exhibited emulsification activities against p -xylene (E24 = 71.43% ± 1.43), diesel oil (E24 = 14.71% ± 0.29) and n -hexadecane (E24 = 25.71% ± 0.57) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the bioavailability of hydrocarbons, microorganisms produce biosurfactants [ 107 , 108 ]. The biosurfactants produced by bacteria can also contribute to inhibiting the growth of phytopathogens, help colonize plant tissues and improve bacterial motility [ 109 ]. In this study, the ZCR6 strain produced a surface-active compound, which showed a positive result for the oil-spreading test and exhibited emulsification activities against p -xylene (E24 = 71.43% ± 1.43), diesel oil (E24 = 14.71% ± 0.29) and n -hexadecane (E24 = 25.71% ± 0.57) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The species Pseudomonas fluorescens, P. putida, P. cepacia, and P. chlororaphis showed high antagonistic activity against polyphagous fungi [84,85]. Pseudomonas fluorescens BRZ63 inhibited mycelium growth of Rhizoctonia solani, Colletotrichum dematium, Sclerotinia sclerotiorum, and Fusarium avenaceum [86].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of plant-growth-promoting bacteria with the host plant is complex. The beneficial effects are associated with the bacterial ability to produce IAA, nutrients (ammonia, phosphate), surfactants, siderophores, or enzymes that attack the cell wall polysaccharides in fungal pathogens [ 51 ]. Other mechanisms strengthen the plant cell wall, prevent an excessive production of the plant hormone ethylene [ 51 ], or change the distribution of the plant hormone abscisic acid [ 52 ].…”
Section: Potentiality Of the Aldoxime-nitrile Pathway In Plant-associ...mentioning
confidence: 99%
“…It supports germination and growth, triggers plant resistance mechanisms, and also has nematocidal activity [ 60 ]. However, IAA only has plant-promoting effects within a restricted range of concentrations [ 51 ]. The regulation of IAA production in bacteria is also sensitive to environmental factors [ 10 ].…”
Section: Potentiality Of the Aldoxime-nitrile Pathway In Plant-associ...mentioning
confidence: 99%
See 1 more Smart Citation